MENGEMBANGKAN SOFT SKILL SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI SMKN 3 PALANGKA RAYA - Agustina, Meylinda; Muslimah, Muslimah; Gofur, Abdul (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This research was conducted with the intention of developing students' soft skills through the implementation of the Problem Based Learning (PBL) learning model in Islamic Religious Education subjects at SMKN 3 Palangka Raya. Non-technical skills such as critical thinking skills in solving problems, effective interpersonal communication, and collaboration in groups, are important aspects that students must have in order to face challenges in the professional world. The research approach used was Classroom Action Research (CAR), by adopting the spiral model from Kemmis and McTaggart which includes the stages of planning, action, observation, and reflection. A total of 30 students from class X Culinary 2 were used as subjects in this study, but only 28 students were consistently involved in each learning cycle. The analysis technique used was descriptive quantitative, with data collection methods in the form of observation, questionnaire distribution, documentation, and in-depth interviews. The findings showed that the percentage of soft skill mastery increased, from 76.48% in the first cycle to 78.00% in the second cycle, both of which were included in the "good" category. This fact indicates that the implementation of well-designed and contextually appropriate problem-based learning can encourage significant improvements in the development of students' soft skills. ABSTRAKPenelitian ini dilaksanakan dengan maksud untuk mengembangkan kecakapan soft skill peserta didik melalui implementasi model pembelajaran Problem Based Learning (PBL) dalam mata pelajaran Pendidikan Agama Islam di SMKN 3 Palangka Raya. Keterampilan non-teknis seperti kemampuan berpikir kritis dalam menyelesaikan masalah, komunikasi interpersonal yang efektif, serta kolaborasi dalam kelompok, merupakan aspek penting yang harus dimiliki oleh siswa guna menghadapi tantangan di dunia profesional. Pendekatan penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK), dengan mengadopsi model spiral dari Kemmis dan McTaggart yang mencakup tahapan perencanaan, tindakan, pengamatan, serta refleksi. Sebanyak 30 peserta didik dari kelas X Kuliner 2 dijadikan subjek dalam penelitian ini, namun hanya 28 orang yang secara konsisten terlibat dalam setiap siklus pembelajaran. Teknik analisis yang digunakan adalah deskriptif kuantitatif, dengan metode pengumpulan data berupa observasi, penyebaran kuesioner, dokumentasi, serta wawancara mendalam. Temuan menunjukkan bahwa persentase penguasaan soft skill mengalami peningkatan, dari 76,48% pada siklus pertama menjadi 78,00% pada siklus kedua, yang keduanya masuk dalam kategori “baik”. Fakta ini mengindikasikan bahwa penerapan pembelajaran berbasis masalah yang dirancang dengan baik dan sesuai dengan konteks dapat mendorong peningkatan signifikan dalam pengembangan kemampuan soft skill siswa.